SAT0541 Analysis of Health Care Costs Associated with Ankylosing Spondylitis in Turkey. (23rd January 2014) - Baser, O.; Burkan, A.; Baser, E.; Koselerli, R.; Ertugay, E.; Altinbas, A.
Abstract : Background: The economic burden of ankylosing spondylitis (AS) has been analyzed in other countries, yet it is not well documented in Turkey. Therefore, Turkey has invested in MEDULA, a nationwide integrated system between health insurance and healthcare providers. Objectives: To explore healthcare costs associated with AS in Turkey using nationwide real-world data. Methods: Using International Classification of Disease Tenth Revision Clinical Modification (ICD-10-CM) codes, adult prevalent and incident AS patients (age 18-99) with two AS-related visits at least 60 days apart, identified between 06/01/2010 and 12/31/2010, with 1 year of continuous health plan enrollment for the baseline and follow-up years were included in the study. Pharmacy, outpatient and inpatient claims were compiled over the study period. Generalized linear models were used to estimate expected annual costs, controlling for baseline demographic and clinical characteristics. Results: Total 2, 986 patients were identified (603 incident, 2, 383 prevalent cases). Most subjects were age 18-39 years (58% incident, 51% prevalent) and 44% of incident and 38% of prevalent cases were female. Prevalent patients had higher comorbidity index scores (6.04 vs. 2.24, p<0.001). Risk-adjusted total annual medical costs were €2, 253 for incident and €4, 233 for prevalent patients. Pharmacy costs accounted for most of the total costs (89% prevalent; 77% incident). Image/graph: Conclusions: Findings suggest that AS health care costs in Turkey resemble those in Europe. Costs are driven by comorbidities and treatment choices. Current data provides a baseline to evaluate economic effect of AS-related treatment and policy. Disclosure of Interest: None Declared